INFRACȚIUNILE CONTRA PATRIMONIULUI ÎN DREPTUL MEDIEVAL ROMÂNESC - Igor CIOBANU; Artur COTRUȚĂ (Studia Universitatis Moldaviae: Stiinte Sociale, 2019)
This article reflects the issues related to the approach of crimes and the application of sanctions in the criminal norms of the Romanian criminal law through the principles specific to the investigated epoch. The oldest written criminal regulations were the comments of the Byzantine jurists, and then there were printed the rules of the rulers Vasile Lupu and Matei Basarab. To the crimes against patrimony it was given special attention both in the Law of the Country and the rules elaborated at the Iasi and Bucharest courtyards. The sanctions, in particular, were pecuniary in case of recidivism and corporal or capital, depending on the object of the crime and the status of the victim.